Marketing Strategy Using Instagram Influencers to Increase Sales - Daswan, Lestari; Desi Lestari, Tri; Faradilla, Zahrah; Ramadana, Sri (Robust: Research of Business and Economics Studies, 2026)
This study aims to analyze Hisana Fried Chicken's marketing strategy through Instagram in Kendari City, and to determine and understand the impact of content created by Instagram influencers on increasing Hisana Fried Chicken sales in Kendari City. This study used a qualitative method, with 10 informants. The results showed that the marketing strategy through Instagram influencers proved effective in increasing Hisana Fried Chicken sales. Hisana's sales increase in several outlets reached around 20-40%, especially when there were promotions supported by influencers. Hisana is advised to continue strengthening collaboration with influencers who have credibility, high engagement rates, and audiences relevant to the brand's market segment. Credibility has been proven to be more influential than mere popularity. The conclusion of this study illustrates that Instagram influencer-based digital marketing is a strategy that can be used as a reference in efforts to increase Hisana Fried Chicken's sales and presence in a competitive market. Therefore, the development and management of influencer strategies need to be carried out in a planned and sustainable manner to achieve maximum results.